Effect of Shot Peening on Fatigue Properties for Corroded and Uncorroded (CK35) Steel - Arbilei, Marwan N.; Hamed, Jamal Mohammed (Al-Khwarizmi Engineering Journal, 2019)
The traction property is one of the important mechanical properties, especially the rotary parts which are subjected to constant and variable loads There are many methods used to improve this property, and the shoot peening by metal balls is considered the most critical one. the study focuses on this characteristic of steel CK35 used in many engineering applications as the rotating shafts and railway This study shows that the fatigue strength is improved by14% after shoot peening with metal balls. The study includs the rehabilitation of damaged samples as a result of fatigue corrosion. The standard solution adopted was 36% MgCl2 with a 30 days immersion period. These samples has been improved by 6% after it decreased by18% due to immersion in the alkaline solution.